Pattern of Diversity and Regeneration Potential along Altitudinal Gradient in Selected Forest Stands of Kumaun Himalaya - Joshi, Vinod Chandra; Chandra, Naveen (Indian Forester, 2020)
Forest diversity is the main source of livelihood of the people living in the Kumaun Himalaya, and vegetation diversity of forest depends on the several climatic, and topographic factors. The aim of the present study is to investigate altitudinal gradient in species composition, diversity, species richness and regeneration potential with special reference to density, frequency, species diversity and concentration of dominance. The study was conducted in selected forest stands of Almora Forest Division in the Kumaun Himalaya, along elevation gradient of 1200-1950m altitude in three altitudinal gradients i.e. hill base (Vishwanath) hill slope (Palna) and hill top (Banari Devi). Pinus roxburghii was the most dominant species in hill base and hill slope while Quercus leucotrichophora was the dominated species in hill top. In different layers, density varied from 472 to 1194 ind/ha (tree layer), 49-560 ind/ha (sapling) and 350-1428 ind/ha (seedlings). The species diversity ranges from 1.26 to 2.99 for trees, 0.89 to 3.03 for sapling and 0.60 to 1.48 for seedlings. The maximum density of trees was recorded in the hill top while it was found minimum in hill base of study sites. The total basal area was found ranges from 27.95-54.87 m2/ha for tree layer and 0.23-0.40 m2/ha for sapling. On the basis of density of seedlings, saplings and trees, the regeneration potential in all three altitude was fair.